Korelace mezi tréninkovým režimem a výsledky ceského poháru junioru ve slasomu a sjezdu u žen - Krausová, T. (Univerzita Palackého v Olomouci, 2023)
The aim of this work was to determine the relationship between training load indicators and results in the Czech Junior Cup in women's slalom and wildwater canoe. I compared the training diaries of six female competitors with their results in the K1 and C1 within the Czech Junior Cup 2022 in slalom and whitewater canoe. I determined the correlation between training load indicators and results in the Czech Junior Cup in slalom and wildwater canoe using the Sperman correlation coefficient. For the K1 and C1 slalom, there was a strong association between results in the CJC and slalom training (r= -.83 and -.77, p <0.05). A moderately strong association for strength and running training (r= -.54 and -.60, p <0.05). The strongest association between results at the CJC whitewater canoeing was for category C1 in strength training (r= -.89, p <0.05). A moderately strong association was found between results in categories K1 and C1 and specific training (r= -.49 and -.31, p<0.05). For the K1, a moderately strong association was also found between results in CPC wildwater canoe and slalom training (r= -.54, p <0.05). The results show that to achieve high performance in slalom, specific fitness training and technique training are irreplaceable.